Pemahaman Jurnalis Lokal Dalam Peliputan Pemilu 2019 Di Sumatera Utara - Muhammad Thariq; Ribut Priadi (Universitas Medan Area, 2019)
This study aims to look at the level of understanding of local journalists in the coverage of the 2019 Elections in North Sumatra. The method used is a qualitative-descriptive approach using observation and in-depth interviews with mainstream print media journalists, online media journalists and professional organizations. The results of the study show that local journalists' understanding of their profession has not shown significant encouraging developments so that the coverage of the 2019 Elections is relatively similar to the 2014 elections. For this reason, the journalists have not utilized the election momentum to increase their understanding of the profession in accordance with public expectations and the Press Council to journalists so that making Elections a means of political education, improving the quality of democratic society and contributing to the success of quality elections. There are still journalists who find it difficult to leave alignments with certain groups of supporters and candidates on the basis of ideological similarities.